Research on operators' big data technologies and applications - Tao CHEN; Meng LU; HENYanming C (Dianxin kexue)
The rapid development of big data technology provides fast mass data processing method for operators' traditional businesses,such as network planning and optimization,but also laid the data foundation for new businesses,such as credit,personalized recommendations,internet services.It is important to the development of the industry.The big data processing cutting-edge technology was studied,relative engineering experience and key issues were introduced,reference for other researcher was provided.